Exploring The Washback Effect of Summative Assessment on Junior High Schools Efl Students: Insight From Teachers' Perspectives - Faidatuz Zahroini Hasyim; Nunung Nurjati; Endah Yulia Rahayu (EduInovasi: Journal of Basic Educational Studies, 2025)
This study examines the impact of summative assessments on English language learning in junior high schools from teachers' perspectives. Summative assessments, which evaluate students' learning outcomes at the end of an instructional period, significantly influence teaching strategies and student motivation. The purpose of this study is to explore how teachers perceive and respond to the effects of summative assessments in their classrooms. This research employs a qualitative approach using thematic analysis, with data collected through interviews with junior high school English teachers. The findings reveal that some teachers consider summative assessments as a motivation for students to study harder, while others believe their effectiveness is influenced by students' backgrounds and motivation levels. Furthermore, teachers modify their instructional approaches based on assessment results to enhance learning effectiveness. The study concludes that the impact of summative assessments is complex, shaped by various internal and external factors, and highlights the importance of reflective teaching practices. The implications of this research can contribute to developing more effective assessment strategies to improve student learning outcomes.